1998
DOI: 10.1097/00007890-199810270-00009
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variation in the Transforming Growth Factor-??1 Gene

Abstract: The production of TGF-beta1 is under genetic control, and this in turn influences the development of lung fibrosis. Hence, the TGF-beta1 genotype has prognostic significance in transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 586 publications
(144 citation statements)
references
References 23 publications
3
134
0
7
Order By: Relevance
“…We hypothesized that the increased frequency of hyperexpression of TGF-␤ 1 may contribute to the excess burden of ESRD in blacks. We also have suggested that hyperexpression of TGF-␤ 1 might be genetically determined, because DNA polymorphisms in codon 25 of the TGF-␤ 1 gene have been associated with hypertension (20) and codon 10 polymorphisms have been associated with lung fibrosis (21).…”
mentioning
confidence: 99%
“…We hypothesized that the increased frequency of hyperexpression of TGF-␤ 1 may contribute to the excess burden of ESRD in blacks. We also have suggested that hyperexpression of TGF-␤ 1 might be genetically determined, because DNA polymorphisms in codon 25 of the TGF-␤ 1 gene have been associated with hypertension (20) and codon 10 polymorphisms have been associated with lung fibrosis (21).…”
mentioning
confidence: 99%
“…Some of these polymorphisms seem to be correlated to its production [18][19][20][21][22][23][24][25], and potentially conferring flexibility to immune response. The presence of certain genotypes may influence the course of both viral and bacterial infections [13,[26][27][28][29], as well as be associated to susceptibility or resistance to auto-immune diseases [30,31], or influence both solid organ post-transplant rejection processes [32,33], and graft versus host disease post bone-marrow transplantation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the regulatory regions of several cytokine genes may cause inter-individual differences in cytokine production (Wilson et al, 1997;Turner et al, 1997;Awad et al, 1998;Fishman et al, 1998;Pravica et al, 1999). As these polymorphisms segregate independently, each person is a mosaic of high-, intermediate-, and low-producing phenotypes.…”
Section: Cytokine Gene Polymorphismsmentioning
confidence: 99%